2004
DOI: 10.4049/jimmunol.173.3.2041
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Methimazole Inhibits TNF-α-Induced VCAM-1 Expression in an IFN Regulatory Factor-1-Dependent Manner and Reduces Monocytic Cell Adhesion to Endothelial Cells

Abstract: Proinflammatory cytokine (e.g., TNF-α)-induced expression of endothelial cell adhesion molecules (ECAMs) on the lumenal surface of the vascular endothelium and a consequent increase in leukocyte adhesion are key aspects of pathological inflammation. A promising therapeutic approach to diminish aberrant leukocyte adhesion is, therefore, to inhibit cytokine-induced ECAM expression at the transcription level. Several studies suggest that methimazole, a compound used clinically to treat autoimmune diseases, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 43 publications
6
48
0
1
Order By: Relevance
“…The early induction of CD38 in ASM cells by cytokine combination observed here does not seem to involve an NF-kB-dependent pathway, since we found that NF-kB activation is dramatically inhibited in TNF-a/IFN-g-treated cells at these time points (31). Instead, we investigated a possible role of the transcription factor IRF-1 based on multiple indirect lines of evidence: first, IFNs and retinoic acids, the classical inducers of IRF members (24,25,32), up-regulate CD38 expression in different cell types, including ASM cells (14,33,34); second, three IRF-1-binding sites are present in the 59 flanking region of the human CD38 gene (35), although their functional role has not yet been demonstrated in any cell types. We previously reported that TNF-a induced an early and sustained activation of IRF-1 in human ASM cells (21).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The early induction of CD38 in ASM cells by cytokine combination observed here does not seem to involve an NF-kB-dependent pathway, since we found that NF-kB activation is dramatically inhibited in TNF-a/IFN-g-treated cells at these time points (31). Instead, we investigated a possible role of the transcription factor IRF-1 based on multiple indirect lines of evidence: first, IFNs and retinoic acids, the classical inducers of IRF members (24,25,32), up-regulate CD38 expression in different cell types, including ASM cells (14,33,34); second, three IRF-1-binding sites are present in the 59 flanking region of the human CD38 gene (35), although their functional role has not yet been demonstrated in any cell types. We previously reported that TNF-a induced an early and sustained activation of IRF-1 in human ASM cells (21).…”
Section: Discussionmentioning
confidence: 93%
“…IRF-1 is an important transcriptional factor involved in the regulation of TNF-a-and IFN-inducible genes (24,25). To date, little is known as to whether cytokines and steroids modulate IRF-1 expression and/or function in ASM cells.…”
Section: Irf-1 Induction By Tnf-a and Ifn-g Combination In Asm Cells mentioning
confidence: 99%
“…Since C10 has been shown to block TLR signaling in other cell types (Dagia et al 2004, Harii et al 2005, McCall et al 2007, Schwartz et al 2009), we questioned whether C10 may be blocking TLR signaling in 3T3L1 cells and RAW 264.7 macrophages. TLR4 signaling has been implicated in the development of insulin resistance (Lin et al 2000, Shi et al 2006; thus, we questioned whether C10 could inhibit LPSinduced inflammatory signaling in these cell lines.…”
Section: C10 Blocks Palmitate-mediated Up-regulation Of Socs-3 Expresmentioning
confidence: 99%
“…We have previously shown that phenylmethimazole (C10) is effective in blocking toll-like receptor (TLR)-mediated activation of inflammatory pathways in non-immune cells (Dagia et al 2004, Harii et al 2005, McCall et al 2007, Schwartz et al 2009). Given that adipose tissue and associated macrophages are important sources of inflammatory molecules that mediate insulin resistance, we investigated the ability of C10 to block inflammatory pathways in 3T3L1 adipocytes and RAW 264.7 macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании T.A. White et al (2006) продемонстри ровано прямое влияние TNF α на сократимость гладких мышц дыхательных путей [45]. Некоторыми исследователями показано также, что TNF α и IFN регулируют экспрессию множества провоспалитель ных генов, включая цитокины, хемокины, факторы роста в ГМК [37,46], а экспрессия CD38 повышает ся при синергичном действии TNF α и IFN γ в ГМК дыхательных путей [41].…”
Section: обзорыunclassified